Kinetics of Amyloid β Monomer-to-Oligomer Exchange by NMR Relaxation - Fawzi, Nicolas L; Ying, Jinfa; Torchia, Dennis A; Clore, G. Marius (Journal of the American Chemical Society, 2010)
Recent studies have implicated non-fibrillar oligomers of the amyloid β (Aβ) peptide as the primary toxic species in Alzheimer’s disease. Detailed structural and kinetic characterization of these states, however, has been difficult. Here we use NMR relaxation measurements to address the kinetics of exchange between monomeric and large, polymorphic oligomeric species of Aβ(1−40). 15N and 1HN R 2 data at multiple magnetic fields were recorded for several peptide concentrations subsequent to the establishment of a stable pseudo-equilibrium between monomeric and NMR-invisible soluble oligomeric species. The increase in 15N and 1HN R 2 rates as a function of protein concentration is independent of nucleus and magnetic field and shows only a small degree of variation along the peptide chain. This phenomenon is due to a lifetime broadening effect arising from the unidirectional conversion of monomer to the NMR-invisible oligomeric species (“dark” state). At a total Aβ(1−40) concentration of 300 μM, the apparent first-order rate constant for this process is ∼3 s−1. Fitting the McConnell equations for two dipolar-coupled spins in two-site exchange to transfer-of-saturation profiles at two radiofrequency field strengths gives an estimate for k off of 73 s−1 and transiently bound monomer 1HN R 2 rates of up to 42 000 s−1 in the tightly bound central hydrophobic region and ∼300 s−1 in the disordered regions, such as the first nine residues. The fraction of peptide within the “dark” oligomeric state undergoing exchange with free monomer is calculated to be ∼3%.